2019
DOI: 10.1080/24749508.2019.1571670
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of heavy metals and salts for human and irrigation consumption of groundwater in Qambar city: a case study

Abstract: The study investigated the water quality of groundwater for consumption of human beings and irrigation of taluka Qamber district Qamber-Shahdadkot, Sindh, Pakistan. A total of 21 representative groundwater samples were collected mostly used for human consumption. According to the research work, 81% samples were not suitable for drinking purpose with TDS above the maximum permissible limit of WHO (1000 mg/L). The pH, total phosphate-P, orth ophosphate-P, nitrate-N, nitrite-N, and arsenic were within WHO limits.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 27 publications
1
21
0
1
Order By: Relevance
“…The elements Na, K, Ca, Mg, Cr, Co, Ni, Mn, Zn, Pb, Fe, Cu and Cd were examined using (Perkin Elmer AA-800, Singapore) flame atomic absorption spectrophotometer (FAAS) at mentioned conditions by manufacturer. The minerals examination was measured in triplicate (n = 3) with delay time 4 s and integration time 4 s (Lanjwani et al., 2019; Pohl., et at., 2017). Instrument (FAAS) was controlled by the Win Lab software with computer (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…The elements Na, K, Ca, Mg, Cr, Co, Ni, Mn, Zn, Pb, Fe, Cu and Cd were examined using (Perkin Elmer AA-800, Singapore) flame atomic absorption spectrophotometer (FAAS) at mentioned conditions by manufacturer. The minerals examination was measured in triplicate (n = 3) with delay time 4 s and integration time 4 s (Lanjwani et al., 2019; Pohl., et at., 2017). Instrument (FAAS) was controlled by the Win Lab software with computer (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…12). A similar study reported higher values of water quality parameters of drinking water of Qamber-Shahdad District [43].…”
Section: Resultsmentioning
confidence: 54%
“…Sejauh ini, air tanah masih sangat banyak dijumpai penggunaannya [5] sebagai suplay kebutuhan harian manusia [6]. Media yang digunakan dapat berupa sumur tanah [7] maupun sumur bor [8].…”
Section: Pendahuluanunclassified